2023
DOI: 10.3389/fimmu.2023.1292146
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of macrophage infiltration and polarisation based on integrated transcriptomic and histological analyses in Primary Sjögren’s syndrome

Yuan Zong,
Yi Yang,
Jiawen Zhao
et al.

Abstract: BackgroundPrimary Sjögren’s syndrome (pSS) is a progressive inflammatory autoimmune disease. Immune cell infiltration into glandular lobules and ducts and glandular destruction are the pathophysiological hallmarks of pSS. Macrophages are one of the most important cells involved in the induction and regulation of an inflammatory microenvironment. Although studies have reported that an abnormal tissue microenvironment alters the metabolic reprogramming and polarisation status of macrophages, the mechanisms drivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Studies have shown that macrophage are consistently present in the affected SG of SS patients and their abundance is positively correlated with the focality index. Activated macrophage produce inflammatory cytokines that result in damage to SGECs ( 113 ). macrophage exhibit high plasticity, differentiating into either classically activated (M1 type) or alternatively activated (M2 type) macrophage in response to various microenvironmental stimuli.…”
Section: Common Cells Types and Pathologic Mechanisms In Ssmentioning
confidence: 99%
“…Studies have shown that macrophage are consistently present in the affected SG of SS patients and their abundance is positively correlated with the focality index. Activated macrophage produce inflammatory cytokines that result in damage to SGECs ( 113 ). macrophage exhibit high plasticity, differentiating into either classically activated (M1 type) or alternatively activated (M2 type) macrophage in response to various microenvironmental stimuli.…”
Section: Common Cells Types and Pathologic Mechanisms In Ssmentioning
confidence: 99%
“…Human studies have provided evidence of macrophage infiltration in the salivary glands of pSS patients, which has been correlated with disease severity [ 2 , 3 ]. Analysis of single-cell RNA sequencing data demonstrated that macrophages are among the most abundant innate immune cells in peripheral blood mononuclear cells (PBMCs) and glandular tissues in pSS patients [ 4 ]. Additionally, research conducted using murine models of pSS suggests that macrophages may act as a mediator between CD4 + T cells and local tissue damage [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%